O novo templo de Salomão: o projeto de expansão da Igreja Universal do Reino de Deus para o Brasil e o mundo. - Costa, Rafael Vilaça Epifani (2017)
The construction of the Temple of Solomon in this work named as New Temple of Solomon was announced in 2010 by Bishop Edir Macedo as a great project to be held in São Paulo City by the Universal Church of the Kingdom of God (UCKG). Since its birth in 2014, in addition to a "convertion" of its aesthetics (or appearance) applied in this sacred space with the use of objects, vestments and decoration with Jewish motifs -, the UCKG praxis underwent substantial changes; which include doctrinal, discursive, liturgical, architectural, and symbolic aspects that affected all temples from this denomination. Such changes directly reflect the sense that the UCKG is trying to build around the elements that constitute its new sanctuary. The origins, motives and the way in which this process of resignification of the Jewish symbolism, realized by the Universal, is the core to understand what is behind this unique enterprise in world, that was chosen like the main study object of this work. The purpose of this research is to show that, besides being a mega temple. built in the capital of the homonymous state of São Paulo and the maximum symbol of power of the denomination founded by Edir Macedo, the New Temple of Solomon is an expansion project from Universal Church of the Kingdom of God for the next years.